Biomechanical study of human lumbar spine with total disc replacement of maverick prothesis using fem - Zahari, Siti Nurfaezah (2015)
Obesity is one of the concerns that could cause low back pain. Excessive load on the spine could change the mechanical behaviour of the lumbar spine and affected on the pressure and stress that occurs in the intervertebral disc particularly at nucleus pulposus and annulus fibrosus. However, the biomechanical effects of body weight on the lumbar spine and implanted lumbar spine are yet to be fully understood. Thus, the aim of this study was to investigate the biomechanical effects of body weight on the lumbar spine as well as adjacent segments of the implanted lumbar spine. Three dimensional finite element model of the osseoligamentous lumbar spine and implanted lumbar spine models was developed and verified with previous studies. The finite element model was subjected to follower compression load of 500 N, 800 N and 1200 N to represent the load case of normal, overweight and obese with a combination of pure moments of 7.5 Nm in flexion and extension. Increasing weight shows significant effect on the kinematics of the lumbar spine for both finite element models. The excessive load on the lumbar spine increased the pressure and stress that occurs in the intervertebral disc, particularly at the nucleus pulposus and annulus fibrosus. The nucleus pressure was higher in flexion and increased as the compressive load was increased. This phenomenon could contributes to the earliest stages of disc degeneration which occurs in the nucleus pulposus. However, increasing weight were more severe in extension as its results in increased the annulus stress, particularly at posterior intervertebral disc up to 17%. Besides, the increasing weight on the implanted lumbar spine also has the potential to alter the movement of the lumbar spine during flexion and extension motions. The presence of a higher weight applied on the implanted lumbar spine and rigidity of Maverick prosthesis at the operated segment of L4-L5 was suggested as a contributing factor to accelerate in changing the kinematics of the implanted lumbar spine. The changes in kinematics of the implanted lumbar spine gave significant effect on the nucleus pressure and annulus stress. Its results in increased the nucleus pressure up to 155% and 124% in annulus stress compared with the non-implanted lumbar spine which observed in the region of L3-L4 lumbar segment. The high stress on the annulus particularly at the posterior of the disc could accelerate annular tear at the disc rim. In conclusion, flexion and extension appears to have differing affects to disc structure. Whilst flexion increases the nucleus pressure, extension results in the increase in the annulus stress. Heavier individuals are expected to experience an increase in stress and pressure of the disc regardless of the position of the spine. Therefore, an increase in body weight of the lumbar spines changed the kinematics of the lumbar spine and causes an increase in the nucleus pressure and annulus stress. This may be a factor that can lead to early intervertebral disc damage particularly at disc rim. Besides, an increase in body weight of the implanted lumbar spine can also expedite the tendency of disc degeneration at adjacent segments and may require additional surgery.